A Comprehensive Framework for Fire Evacuation Modelling - Murni Fatehah, Alias; Al Fahim, Mubarak Ali; Rozlina, Mohamed (Tianjin University, 2024)
Strategic planning for the evacuation of occupants from buildings becomes crucial during disaster response operations, especially in the context of fire emergencies that pose a direct threat to human lives. This study addresses the specific challenges associated with fire evacuation in smart buildings within the Internet of Things environment. Despite their enhanced connectivity and accessibility, these buildings are still vulnerable to crises; therefore, efficient and swift occupant evacuation planning is necessary. Developing a successful evacuation plan for these situations calls for in-depth knowledge of smart building characteristics, evacuation factors, and skilful modelling. In order to overcome this problem, the research proposed a metamodel approach that serves as a modelling grammar and syntax for systematic design. The metamodel is constructed based on common evacuation model terminology and fire emergency variables. Through the use of a graphical editor and model transformation, the metamodel undergoes validation using a model-checking technique. In abstract modelling, this validation technique provides crucial insights into the accuracy and completeness of the metamodel in enhancing the resilience of smart building evacuation systems.